2014
DOI: 10.3354/dao02765
|View full text |Cite
|
Sign up to set email alerts
|

Relating fibropapilloma tumor severity to blood parameters in green turtles Chelonia mydas

Abstract: Fibropapillomatosis is a neoplastic disease that is commonly found in the green turtles Chelonia mydas in tropical and subtropical regions of the world. In the current project, juvenile green turtles were captured with large-mesh tangle nets in the Indian River Lagoon and on nearshore reefs of Indian River County, Florida, USA, in 1998 and 1999. The purpose of the study was to determine the relationship between the severity of the disease and the general health of green turtles as indicated by blood parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 20 publications
(8 reference statements)
1
17
1
Order By: Relevance
“…Studies on haematological and biochemical parameters have indicated reference intervals for green turtles, and contribute to the determination of their health status; a helpful tool in decision-making regarding rehabilitation and release (Bolten & Bjorndal, 1992; Aguirre et al ., 1995; Hasbún et al ., 1998; Samour et al ., 1998; Hamman et al ., 2006; Flint et al ., 2010; Fong et al ., 2010; Osborne et al ., 2010; Labrada et al ., 2010 a , 2010 b ; Anderson et al ., 2011; Hirama et al ., 2014; Lewbart et al ., 2014). Variability in haematological and biochemical values may also occur in healthy turtles according to their geographic location, habitat, genetics, maturity, sex, breeding and migratory status, and diet (Herbst & Jacobson, 2003; Stamper et al ., 2005; Deem et al ., 2006; Hamann et al ., 2006; Whiting et al ., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on haematological and biochemical parameters have indicated reference intervals for green turtles, and contribute to the determination of their health status; a helpful tool in decision-making regarding rehabilitation and release (Bolten & Bjorndal, 1992; Aguirre et al ., 1995; Hasbún et al ., 1998; Samour et al ., 1998; Hamman et al ., 2006; Flint et al ., 2010; Fong et al ., 2010; Osborne et al ., 2010; Labrada et al ., 2010 a , 2010 b ; Anderson et al ., 2011; Hirama et al ., 2014; Lewbart et al ., 2014). Variability in haematological and biochemical values may also occur in healthy turtles according to their geographic location, habitat, genetics, maturity, sex, breeding and migratory status, and diet (Herbst & Jacobson, 2003; Stamper et al ., 2005; Deem et al ., 2006; Hamann et al ., 2006; Whiting et al ., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…28 Other external body features, such as the presence or absence of fibropapilloma (FPs), epibiotic load, and body condition also provide information about the general health of individuals. 11,19,37 Diseases in green turtles, including fibropapillomatosis, have been connected to heavily polluted areas, agricultural runoff, and areas with high human density. 4 FPs are associated with infection by chelonid herpesvirus 5 (species Chelonid alphaherpesvirus 5).…”
Section: Introductionmentioning
confidence: 99%
“…Schaefer et al (2011) found a positive correlation between the number of IRL bottlenose dolphins colonized by Escherichia coli and the number of septic tanks in the area they lived; with the highest number of both being in the northern segments of the IRL. Similarly, the health of juvenile green sea turtles Chelonia mydas Linnaeus as measured through blood parameters and the severity and prevalence of fibropapillomatosis (caused by an alphaherpesvirus) was significantly poorer in the IRL population than those captured on adjacent nearshore wormrock reefs (Hirama et al, 2014).…”
mentioning
confidence: 99%